Hypertension management in a population of older adults in rural South Africa - Jardim, Thiago Veiga; Bärnighausen, Till (Journal of hypertension, 2017)
Objective: Assess awareness, treatment, and control of hypertension, as an indication of its management, in rural South Africa, especially regarding modifiers of these variables. Methods: A population-representative sample of adults aged at least 40 years residing in the rural Agincourt subdistrict (Mpumalanga Province) covered by a long-term health and sociodemographic surveillance system was recruited. In-person interviews, physical exams, and dried blood spots were collected. Hypertension awareness, treatment, and control rates were assessed. A regression model was built to identify predictors of those outcomes. Results: The mean age of the 2884 hypertensive participants was 64.1 ± 12.7 years. Hypertension awareness rate was 64.4%, treatment among those aware was 89.3 and 45.8% of those treated were controlled. Considering aware and unaware hypertensives, treatment rate was 49.7% and control 22.8%. In the multivariable regression model, awareness was predicted by female sex, age at least 60 years, higher social economic status, prior cardiovascular disease (CVD), nonimmigrant status, literacy, and physical limitation. Improved control among those treated was predicted by age at least 60 years. Blood pressure control among all hypertensive study participants was predicted by female sex, being HIV-negative, age at least 60 years, nonimmigrant status, and prior CVD. Conclusion: High rates of awareness and treatment of hypertension as well as good levels of control were found in this population, probably explained by the long-term surveillance program conducted in the area. Considering the predictors of hypertension management, particular attention should be given to men, residents younger than 60 years, immigrants, and study participants without CVD as these characteristics were predictors of poor outcome.